"Czym ma być dziennik? Wszystkim. Co zawierać? Tylko rzeczy niektóre". O praktyce diarystycznej Bogdana Wojdowskiego = "What is the diary? Everything. What should it contain? Only some things". On Bogdan Wojdowski's diary practices - Majdosz, Sylwia (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The following paper discusses the main aspects of Bogdan Wojdowski's unpublished diary. The author of "Bread for the departed" ["Chleb rzucony umarłym"] started keeping the diary in his early professional life and continued until his death. The paper intends to present selected fragments of the notes which focus on some aspects of Wojdowski's life that established him as a writer of his times.
Keywords: Wojdowski, Bogdan (1930-1994); dziennik; pisarz polski; literatura polska; diary; Polish writer; Polish literature